AXIOLOGICAL FUNDAMENTALS OF ECOLOGICAL CONSCIOUSNESS - Моkliak, Larysa; Pokotylo, Hanna (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The article analyzes and substantiates the axiological foundations of ecological consciousness as the basic and defining component of the ecological culture of the individual and society. The urgency of the topic is determined by the need to find answers to challenges related to the environmental crisis. The authors hold the view that the ecological crisis is a logical manifestation of the social crisis, the destruction of a balanced man-man, community-community, and man-environment relations. History is increasingly approaching the limits of its implementation in terms of production and consumption of material goods. And this highlights the problem of the values of human existence, environmental consciousness, the environmental culture of man, and society as a whole. And it is man, as an intelligent being, capable of critical self-knowledge and self-esteem, to consciously limit himself in his needs and desires, subordinate his activities to the system of cognitive, pragmatic assessments, moral values, and prohibitions and harmonize these relationships. The aim of the article is the definition and specification of the concept of ecological consciousness, analysis, and substantiation of axiological principles of ecological consciousness as a fundamental and determining component of the ecological culture of the individual and society as a whole. Research methods are systemic and interdisciplinary approaches that allow to analyze the subject of the research, namely the formation and functioning of the modern axiological component of environmental consciousness. Research results. Man as a universal creature, endowed with activity, creativity, can act by the standards of any kind and create the specific, inherent form of existence, i.e. a world of culture in which specific moments of life are preserved and actualized as the materialpractical experience of world development, as well as spiritual-theoretical and spiritual-practical knowledge, experience, evaluation, search for meaning and principles of human existence and a system of values. Discussion. The practice of modern life does not remove from the agenda of conscious cultivation of the system of spiritual values both at the individual level and at the level of the social group and society as a whole. Moral values, as a defining element of moral consciousness, give spiritual certainty to both motives and the moral activity itself. Conclusion. Overcoming the current environmental crisis, creating coexistence with nature become possible only on the basis of responsibility, knowledge, care, and recognition of the dignity and rights of the natural world.